(untitled) (Papeles, 2026)
Introduction: This study analyzes the relationship between reading, writing, and mental arithmetic in primary school students using data from the Sistema de Alerta Temprana (SisAT). The objective is to identify how these skills are connected to academic performance and to provide evidence that can guide teaching practices and educational decision-making. Methodology: The research was conducted in a primary school in Ciudad Delicias (Chihuahua), with a population of 324 students from first to sixth grade. A quantitative approach and an ex post facto design were applied, using data from quarterly assessments in Spanish and mathematics, as well as SisAT tests in reading, writing, and mental arithmetic. Statistical analysis was performed with IBM SPSS Statistics. Results and discussion: The findings indicate a significant correlation between reading and writing, while reading shows a positive relationship with academic performance. In contrast, writing and mental arithmetic display low correlations with school grades. These results suggest that strengthening reading skills directly impacts academic achievement, while writing and mental arithmetic require specific pedagogical strategies to enhance their influence on learning. Conclusions: It is concluded that the use of SisAT as an early warning system enables the timely identification of learning difficulties, the design of personalized interventions, and the promotion of students’ comprehensive development, ensuring solid training in basic competencies at the primary education level.